Multi-material, multi-technology FDM: exploring build process variations. Issue 3 (14th April 2014) - Espalin, David; Alberto Ramirez, Jorge; Medina, Francisco; Wicker, Ryan
Abstract : Purpose: – The purpose of this paper is to investigate a build process variation for fused deposition modeling (FDM) in which contours and rasters (also referred to as internal fill patterns) are built using different layer thicknesses and road widths. In particular, the paper examines the effect of the build process variation on surface roughness, production times and mechanical properties. Additionally, a unique FDM process was developed that enabled the deposition of discrete multiple materials at different layers and regions within layers. Design/methodology/approach: – A multi-material, multi-technology FDM system was developed and constructed to enable the production of parts using either discrete multi-materials or the build process variation (variable layer thickness and road width). Two legacy FDM machines were modified and installed onto a single manufacturing system to allow the strategic, spatially controlled thermoplastic deposition with multiple extrusion nozzles of multiple materials during the same build. This automated process was enabled by the use of a build platform attached to a pneumatic slide that moved the platform between the two FDM systems, an overall control system, a central PC and a custom-made program (FDMotion) and graphic user interface. The term multi-technology FDM system used here implies the two FDM systems and the integration of these systems into a single manufacturing environment using the movable platform and associated hardware and software. Future work will integrate additional technologies within this system. Parts produced using the build process variation utilized internal roads with 1, 524 μm road width and 508 μm layer height, while the contours used 254 μm road width and 127 μm layer height. Measurements were performed and compared to standard FDM parts that included surface roughness of planes at different inclinations, tensile testing and fabrication times. Findings: – Results showed that when compared to the standard FDM process, the parts produced using the build process variation exhibited the same tensile properties as determined by a student's t -test ( p -values > 0.05, μ1-μ2 = 0, n = 5). Surface roughness measurements revealed that the process variation resulted in surface roughness (Ra ) improvements of 55, 43, 44 and 38 per cent for respective planes inclined at 10, 15, 30 and 45° from vertical. In addition, for a 50.8 × 50.8 mm square section (25.4 mm tall), the build process variation required a minimum of 2.8 hours to build, while the standard FDM process required 6.0 hours constituting a 53 per cent reduction in build time. Finally, several manufacturing demonstrations were performed including the fabrication of a discrete PC-ABS sandwich structure containing tetragonal truss core elements. Originality/value: – This paper demonstrates a build strategy that varies contour and raster widths and layer thicknesses for FDM that can be used to improve surface roughness – a characteristic that has historically been in need of improvement – and reduce fabrication time while retaining mechanical properties.